2017
DOI: 10.1128/jvi.01555-16
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Hsc70 Is Associated with Cucumber Necrosis Virus Particles and Plays a Role in Particle Disassembly

Abstract: Uncoating of a virus particle to expose its nucleic acid is a critical aspect of the viral multiplication cycle, as it is essential for the establishment of infection. In the present study, we investigated the role of plant HSP70 homologs in the uncoating process of Cucumber necrosis virus (CNV), a nonenveloped positive-sense single-stranded RNA [(ϩ)ssRNA] virus having a Tϭ3 icosahedral capsid. We have found through Western blot analysis and mass spectrometry that the HSP70 homolog Hsc70-2 copurifies with CNV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Recently, Alam et al . reported that Hsc70-2 binds to purified CNV virions and plays a role in disassembly of virus particles 39 . Hsc70 was also reported to participate in the intercellular transport of pepino mosaic virus (PepMV) 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Alam et al . reported that Hsc70-2 binds to purified CNV virions and plays a role in disassembly of virus particles 39 . Hsc70 was also reported to participate in the intercellular transport of pepino mosaic virus (PepMV) 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A cytosolic Hsp70 is found to play multiple roles in TBSV replication, such as the insertion of the viral replication proteins into peroxisomal membranes and activation of TBSV replication by interaction with viral replication proteins 34 38 . Recent studies also indicated that Hsc70 is co-opted by CNV to functions in several aspects of the viral infection cycle, including the positive regulation of viral RNA accumulation, virus particle assembly and disassembly, and targeting of CP to the chloroplasts 27 , 39 . Additionally, a chloroplast Hsp70 isoform was reported to interact with bamboo mosaic virus (BaMV) replicase and is required for the preference of BaMV for older leaves of N .…”
Section: Introductionmentioning
confidence: 99%
“…Preincubation of viral particles with recombinant Hsp70 or antibodies against Hsp70 prevented rotavirus internalization (Guerrero et al 2002;Zarate et al 2003;Perez-Vargas et al 2006), and Hsp70 depletion impaired reovirus disassembly into transcriptionally active particles (Ivanovic et al 2007). In cucumber necrosis virus, Hsp70 was found to directly alter capsid conformation, as determined by electron microscopy (Alam and Rochon 2017). A similar extracellular interaction with Hsp70 was reported for positive-strand RNA viruses of the flavivirus family, for example, hepatitis C virus (HCV) (Parent et al 2009;Khachatoorian et al 2014), Japanese encephalitis virus (JEV) (Das et al 2009), and dengue virus (DENV) (Reyes-Del Valle et al 2005).…”
Section: Entry and Disassemblymentioning
confidence: 98%
“…Blocking HSC70 through specific antibodies significantly inhibits δ release and, complementing with purified HSC70, totally restores the δ-release activity (Ivanovic et al, 2007), suggesting that HSC70 plays central roles in reovirus disassembly. Apart from animal viruses, HSC70 has been reported to be associated with cucumber necrosis virus (CNV) particles and incubation of recombinant HSC70-2 with CNV results in conformational changes or partial disassembly of virus capsid and produces higher numbers of local lesions on Chenopodium quinoa, suggesting that HSC70 plays an important role in plant virus infection (Alam and Rochon, 2017).…”
Section: Hsc70 Involves In Viral Intracellular Trafficking and Disassmentioning
confidence: 99%